Verification of the UR5 robot's properties after a crash caused by a fall of a transferred load from a crane. (17th February 2020) - Semjon, Jan; Janos, Rudolf; Sukop, Marek; Tuleja, Peter; Hajduk, Mikulas; Jurus, Ondrej; Marcinko, Peter; Virgala, Ivan; Vagas, Marek
Installing robots in small businesses is primarily dependent on the ratio of money spent to achieve profit. In addition, from consumer pressure on the production, quality and low cost, the increasing cost of human labour leads to robot deployment. With falling prices of robots, their use is becoming increasingly common, which leads to small firms trying to implement robots that are not new. They try to buy a cheaper older robot or a robot that was damaged during its previous operation. It is necessary to eliminate the risk that arises from more serious damage to the robot, therefore, the requirements for verification of the robot's resultant parameters after its repair performed in own interest. Based on such a requirement, the solution was to verify the parameters of the UR5 robot to confirm the possibility of its further use. After replacing the damaged parts, the robot was subjected to its parameter verification according to standard ISO 9283:2012. For measurement purposes, a measuring cube was designed and manufactured, as well as a measuring nest for Heidenhain sensors.